An Intelligent Image Processing System for Real-Time Detection of Surface Flaws (International Journal of Automation and Smart Technology, 2025)
This paper presents an intelligent parallel image processing system, PVCS (Parallel Visual Computing System), to handle in-line surface defect detection for large objects. PVCS is a parallel expansion of a previously-reported non-destructive Compute Unified Device Architecture (CUDA)-enabled optical inspection system to accommodate large test objects. PVCS is heterogeneous both in terms of hardware and software. From the hardware perspective, PVCS consists of multiple CPUs and GPUs; from the software perspective, PVCS adopts the Message Passing Interface (MPI) and CUDA programming models. A parallel prototype system, consisting of three CPUs and two GPUs, is used to inspect a simulated object with an area eight times greater than that of the real object in our previous work. Given the same resolution requirements, the simulation results show that PVCS can obtain the correct number of defects within a large- size image at a satisfactory processing rate.